Family migration and gender changes. Boundaries, ties and subjectivities - Claudia Santoni (University of Bologna, 2022)
Sociological reflection on migrant families has grown over the years, widening its gaze to highlight the transformations that take place within them and that outline new relational models between the members and between them and the society of arrival. The migration experience changes family relations, modifying intergenerational and even gender relations, a concept that has become a true interpretative category of these modifications. Both family and subjective life practices emerging from studies and research show in the biographical paths taken by first- and second-generation women in Italy, multiform and non-stereotyped identity traits. The concluding part of the essay presents some results from the empirical investigation entitled Gender differences, gender stereotypes and equality aimed at second-generation young people in Italy.